Adiposity and estrogen receptor‐positive, postmenopausal breast cancer risk: Quantification of the mediating effects of fasting insulin and free estradiol. Issue 6 (26th June 2019) - Dashti, S. Ghazaleh; Simpson, Julie A.; Karahalios, Amalia; Viallon, Vivian; Moreno‐Betancur, Margarita; Gurrin, Lyle C.; MacInnis, Robert J.; Lynch, Brigid M.; Baglietto, Laura; Morris, Howard A.; Gunter, Marc J.; Ferrari, Pietro; et al.
Abstract : Adiposity increases estrogen receptor (ER)‐positive postmenopausal breast cancer risk. While mechanisms underlying this relationship are uncertain, dysregulated sex‐steroid hormone production and insulin signaling are likely pathways. Our aim was to quantify mediating effects of fasting insulin and free estradiol in the adiposity and ER‐positive postmenopausal breast cancer association. We used data from a case–cohort study of sex hormones and insulin signaling nested within the Melbourne Collaborative Cohort Study. Eligible women, at baseline, were not diagnosed with cancer, were postmenopausal, did not use hormone therapy and had no history of diabetes or diabetes medication use. Women with ER‐negative disease or breast cancer diagnosis within the first follow‐up year were excluded. We analyzed the study as a cumulative sampling case–control study with 149 cases and 1, 029 controls. Missing values for insulin and free estradiol were multiply imputed with chained equations. Interventional direct (IDE) and indirect (IIE) effects were estimated using regression‐based multiple‐mediator approach. For women with body mass index (BMI) >30 kg/m 2 compared to women with BMI 18.5–25 kg/m 2, the risk ratio (RR) of breast cancer was 1.75 (95% confidence interval [CI] 1.05–2.91). The estimated IDE (RR) not through the mediators was 1.03 (95% CI 0.43–2.48). Percentage mediated effect through free estradiol was 72% (IIE‐RR 1.56; 95% CI 1.11–2.19). There was no evidence for an indirect effect through insulin (IIE‐RR 1.12; 95% CI 0.68–1.84; 28% mediated). Our results suggest that circulating free estradiol plays an important mediating role in the adiposity–breast cancer relationship but does not explain all of the association. Abstract : What's new? Being overweight boosts the risk of breast cancer, but the mechanism is still unclear. Overweight women have higher circulating estrogen levels, which may play a role. Here, the authors calculated the extent to which free estradiol and fasting insulin levels mediated the association between breast cancer and adiposity. They used BMI and waist circumference as measures of adiposity. Using a novel, multiple‐mediator approach, they found that circulating estradiol concentrations accounted for about half of the association between obesity and ER‐positive breast cancer in postmenopausal women. Their analysis found no evidence that insulin plays a role.